Raise your team's employee engagement score : a manager's guide - Finnegan, Richard P. (AMACOM, American Management Association, 2018)
Want employees that go the extra mile? Love them or hate them, employee engagement surveys are here to stay. As manager, you're expected to digest the data and come up with a plan for improving the numbers. But it's not just busy work. Raising engagement scores matters because engagement matters. An enthusiastic workforce translates into higher productivity and profitability with less turnover and absenteeism. Fully committed workers will give their all every day -- and it's your job to make that happen. Forget company picnics or employee-of-the-month awards. For real results, read Raise Your Team's Employee Engagement Score . In this practical, research-based playbook, retention expert Richard Finnegan reveals how to: Build trust with your team Implement stay interviews Develop an employee value proposition Leverage company engagement programs Hire employees who self-motivate Apply smarter, better metrics Measure progress and forecast future engagement And more By following Finnegan's techniques, you'll send those engagement scores through the roof . . . and it won't cost your company a dime.